Algorithm of calculation of water consumption on dairy cattle farm with tied and loose housing at milking in milking parlors - V. V. Gordeev; T. I. Gordeeva; T. Y. Mironova; S. V. Kovalev (Аграрная наука Евро-Северо-Востока, 2024)
Water is used in the whole cycle of milk production, from watering and fodder preparation to washing of milking equipment and milk cooling tanks. At the same time, farms do not control and record the amount of water consumed, which can result in a significant excess of actual water consumption over the normative data. One of the ways to solve this problem can be the introduction of a water consumption monitoring system, which will track the actual water consumption on the farm and compare it with the calculated volume obtained on the basis of normative data, technical characteristics of equipment and animal husbandry technology adopted in the farm. The purpose of the research is to develop an algorithm for calculating water consumption when performing technological operations on cattle dairy farms. As a result of the research, an algorithm for calculating water consumption for technological operations was developed, taking into account different variants of the technical and technological solutions. On the basis of the algorithm a program was developed, with the help of which the sequence of water consumption calculation was tested. The calculation was carried out for a farm for 800 heads of dairy herd of loose housing with productivity of 28 kg/head and 200 heads of loose housing with productivity of 32 kg/head excluding young stock. Water consumption for such a farm is 113.09 m3 /day, of which 99.92 m3 /day is used for watering, fodder preparation, and is non-returnable, and 13.17 m3 /day is used for technological operations. The further direction of research will be the development of a monitoring system based on the developed program of water consumption calculation. In addition to the monitoring system, the program will be useful in technological design of cattle farms for milk production.